Perancangan Sistem E-Commerce Produk Olahan Kain Menjadi Berbagai Macam Pakaian Menggunakan Opencart pada Usaha Home Industry Di Kelurahan Aur Kuning. - Miftahul Jannah, Syadina; Annas, Firdaus; Ruanda, Gita (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The development of information technology opens up great opportunities for home industry businesses to reach a wider market through e-commerce. In this research, an OpenCart-based e-commerce system is designed for businesses that process fabrics into various types of clothing, with the main objective of increasing sales and operational efficiency. So far, the promotion of products from the home industry is often only done through certain applications that are limited to the local market and less known in general. In fact, today's rapidly developing technology allows home industry products to be better known by the wider community, even in the global market. The methodology used in this research includes needs analysis, system design, implementation, and testing, with a focus on implementing the OpenCart platform as a flexible and easy-to-operate e-commerce solution. The main features of the designed system include a complete product catalogue, shopping cart, online payment system, inventory management, and integrated sales reports. OpenCart was chosen due to its ease of use, as well as being supported by a wide community and sufficient resources for further development. The implementation results show that this e-commerce system makes it easier for customers to search, select, and buy products online, and allows businesses to manage orders and stock items more efficiently. The system is also equipped with promotional features and social media integration that expand marketing reach, increase product visibility, and open up sales opportunities in the global market. The evaluation shows that the implementation of OpenCart-based e-commerce has a positive impact, both in terms of revenue and operational efficiency, as well as introducing local products to the international market, which increases product competitiveness in the global market.